Assessment of Stabilized Dredged Sediments using Portland Cement for Geotechnical Engineering Applications along Hurghada Coast, Red Sea, Egypt; Asian Journal of Applied Sciences; Vol. 3, iss. 5 - El-Shinawi A. (2015, 2015)
Title screen